Altered self‐identity and autobiographical memory in epilepsy. (25th November 2015) - Allebone, James; Rayner, Genevieve; Siveges, Benjamin; Wilson, Sarah J.
Summary: Objective: Research suggests that individuals with chronic epilepsy display differences in their self‐identity. The mechanisms by which self‐identity is altered, however, are not well understood. Neural networks supporting autobiographical memory retrieval in the mesial temporal (MT) lobe are thought to be fundamental to self‐identity processes. Thus, we examined differences in self‐identity and autobiographical memory in patients with either MT or non–mesial temporal (NMT) foci with early or late age of habitual seizure onset. Methods: Participants included 102 adults: 51 healthy individuals and 51 patients with drug‐resistant focal seizures (19 MT, 32 NMT). We used the Ego Identity Process Questionnaire to profile the identity development of participants, and examined how this related to memory function assessed using the Autobiographical Memory Test. Results: Patients and controls had strikingly different self‐identity profiles, with early onset MT patients showing the least identity development compared to controls and other patient groups. In contrast, late‐onset NMT patients showed the highest level of identity development of the patient groups and closely resembled healthy controls (p < 0.05 for all comparisons). For all MT patients, poor autobiographical memory retrieval was correlated with altered self‐identity (p < 0.001). No associations between autobiographical memory and self‐identity were evident in the NMT group. Significance: Self‐identity in epilepsy may be modulated by the extent to which seizure foci impinge on the autobiographical memory network and the timing of seizure onset. Early disruption to MT regions of the autobiographical memory network may constitute a neurocognitive mechanism by which self‐identity is altered in chronic focal epilepsy.